The Motives of Medical Students in Tehran University for Choosing Medicine Field and their Outlooks for their Profession: Qualitative versus Quantitative Approach - Saharnaz Nedjat; Hasan Emami Razavi; Arash Rashidian; Shahrooz Yazdani; Reza Majdzadeh (Kerman University of Medical Sciences, 2006)
Background: It seems that in our country choosing medicine as the field of study in university is mostly due to family and society pressures rather than the applicants real interest in this field Objective: To determine medical students motives for choosing medicine and their outlooks for this profession by using two qualitative and quantitative approaches Methods: The qualitative part includes two focus group discussions with interns and one focus group discussion with fresh students In the quantitative part complementary to the qualitative section the causes of choosing medicine field and the rate of students and applicants awareness toward the future statue of their profession were studied For this purpose 33 fresh students 107 interns and 88 applicants of medicine field after taking the entrance examination were selected through convenient and consecutive sampling and were asked to complete the designated questionnaire Results: In the qualitative part everybody agreed that the applicants own preference is not determining and almost all of the students mentioned the social prestige of a physician and medical field as the main cause of choosing this field In the quantitative part interest in the scientific content of this field (in 42%) the role of physician in health improvement (in 21%) financial income (in 143%) the social prestige of physician (in 13%) and the pressure of family and society (in 1%) were mentioned as the main causes of choosing medicine field On the other hand participants in the qualitative part of the study didnt have a good outlook for the professional status of general practitioners and some of them believed that continuing studies in medicine field is more difficult than other fields In the quantitative part of study as the age of participants increased they more asserted that in medical field the possibility of continuing studies finding job in good area and with good income is less compared with other fields Conclusion: The results of this study revealed that many students have not adequate awareness toward the medicine field and in choosing this field they are mostly under the influence of factors such as the pressure of family and the social prestige of the physicians Although these aspects were not obvious in the quantitative part of the study they were confirmed by all of the participants in the qualitative section of the study This fact denotes the importance of qualitative approaches or the combination of qualitative and quantitative designs On the other hand since with increase in the age of students their awareness toward the future statue of their field improves it is suggested that admission is not confined to academic criteria and appropriate metacognitive characteristics of applicants are also considered in admitting the students